Emergence of bulk-like structural features and 2D-to-3D transition in boron nanoclusters - Qiang Chen; Hyun Wook Choi; Guang-Feng Wei; Deniz Kahraman; Rui-Nan Yuan; Qin-Wei Zhang; Qiao-Qiao Yan; Xiao-Ni Zhao; Cai-Yue Gao; Yuan-Yuan Ma; Rui Wei; Yilin Gui; et al. (Proceedings of the National Academy of Sciences, 2025)
As an electron-deficient element, boron possesses fascinating three-dimensional structures and unconventional chemical bonds. Nanoclusters of boron have also been found to exhibit intriguing structural properties, observed to have predominantly planar structures, in stark contrast to bulk boron allotropes, which are composed of the ubiquitous B 12 icosahedral building blocks. Here, we report observation of the 2D-to-3D transition and bulk-like structural features in the size-selected boron clusters, as revealed by photoelectron spectroscopy, chemisorption experiments, and first-principles calculations. In the small to medium cluster size range, planar boron cluster anions are found to be unreactive and only B 46 – and B 56 – are observed to chemisorb C 2 H 4 and CO under ambient conditions, suggesting major structural transitions at these cluster sizes. Notably, B 56 – is also found to be able to chemisorb and activate CO 2 . The global minimum of B 46 – is found to adopt a core-shell structure (B 2 @B 44 – ), consisting of a B 2 core within a B 44 shell, reminiscent of the interstitial B 2 dumbbells in the high-pressure γ -B 28 form of bulk boron. More remarkably, both the global minimum and the second most stable isomer of B 56 – exhibit nest-like configurations, featuring the iconic B 12 icosahedral core surrounded by a B 44 half-shell (B 12 @ h- B 44 – ), signifying the onset of bulk-like structural characteristics in boron nanoclusters.